Synthesis and antimicrobial activities of some thieno[3,2-d][1,3]thiazine nucleosides derivatives - Ghoneim, Amira Atef; Abdelaziz, Sahar (European Journal of Chemistry, 2014)
New thieno[3,2-d][1,3]thiazine nucleosides derivatives were synthesized and structures of the new compounds were confirmed on the basis of elemental and spectral data. Some of the synthesized compounds were screened for antibacterial and antifungal activity.